GE_GERICHTE C/25387/2016 vom 13. März 2017 - GE Cour de justice (2017)
MODIFICATION DES CIRCONSTANCES ; SURENDETTEMENT ; RÉVOCATION DE LA FAILLITE | LP.174.1; LP.174.2; CO.738; LP.192; CO.725.2; CO.743.2;